x = 4, -2
Use the quadratic equation: {-b +/- (b^2 - 4ac)^0.5} / 2a. a = 1, b = -2, c = -8.
2007-06-18 06:56:30
·
answer #1
·
answered by roynburton 5
·
2⤊
0⤋
What you need to do is find factors of -8 that, when added, will sum to -2 (you could use the quadratic formula, but it's really not necessary in this case).
You can break down x²-2x-8 into two expressions, so
x²-2x-8 = (x+n1)(x+n2), where n1 and n2 could be positive or negative.
I'll give you another example, from which you should be able to figure out the answer to your question:
x²-x-6 = 0,
so I need factors of -6 that will add to produce -1. How about -3 and +2?
We now have (x-3)*(x+2) = 0. Using the FOIL method on the left side of the equation, you can see that this mutiplies out to x²-x-6. In this case,
x = 3, and x=-2.
Use this approach for x²-2x-8. Good luck.
2007-06-18 13:57:06
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
There are a number of ways to complete this problem.
Because of its simplicity, I would recommend doing this pronlem by completing the square.
x² - 2x - 8 = 0
(x² - 2x + (-2/2)²) - 8 - (-2/2)² = 0
(x² - 2x + 1) - 8 - 1 = 0
(x-1)² - 9 = 0
x - 1 = â(9)
x - 1 = ± 3
x = ± 3 + 1
x = 4 or -2
2007-06-18 14:04:21
·
answer #3
·
answered by James L 1
·
0⤊
0⤋
x^2 -2x - 8 =0
First factor since -4 times 2 gives -8, then factors are
(x-4)(x+2) = 0 since this also gives the correct mioddle term.
now since you have a product that = 0 then at least one of the factors is 0. Thus either x-4=0 and x=4 or
x+2=0 and x=-2. A quick check in the original equation will show that both are true.
2007-06-18 13:58:39
·
answer #4
·
answered by astronomyccsjr 3
·
0⤊
0⤋
first you need to factor the equation by finding the factors of 8 that have a difference of 2 because the middle term is 2 and the sign on the 8 is negative (subtraction)
8=4*2 and 4-2=2 so the factors of 8 to use are 4 and 2
the equation now factors into 2 binomials and since the middle term in the equation is negative, the negative in the binomials goes with the larger factor (4):
x^2-2x-8 = (x-4)(x+2) = 0
now set each of the factored terms =0
x-4=0
x=4
and
x+2=0
x=-2
2007-06-18 14:00:33
·
answer #5
·
answered by Stop Sine 3
·
0⤊
0⤋
if x^2-2x-8 = 0
this is a quadratic
[-b +- Sqrt( b^2 - 4ac)]/2a
therefore
[2+- Sqrt(4+32)]2
[2+-6]/2
1+-3
the answers are 4 and -2
2007-06-18 14:00:24
·
answer #6
·
answered by jeremy s 2
·
0⤊
0⤋
1.(x-4)(x+2)
so x=4,-2
2.(x-3)(x+2)
so x=3,-2
3.(x-3)(x+1)
so x=3,-1
2007-06-18 14:01:48
·
answer #7
·
answered by selva 1
·
0⤊
0⤋
x² = 2x - 8 = 0
x² - 4x + 2x - 8 = 0
x(x - 4) + 2(x - 4) = 0
(x + 2)(x - 4)
- - - - - - - -s-
2007-06-18 14:26:54
·
answer #8
·
answered by SAMUEL D 7
·
0⤊
0⤋
1. (x-4)(x+2)
x=-2,4
2. (x-3)(x+2)
--------------
(x-3)(x+1)
The x-3 cancels out on the top and bottom.
x+2
-----
x+1
That is your final answer.
2007-06-18 13:56:02
·
answer #9
·
answered by Cool Nerd At Your Service 4
·
0⤊
1⤋